2016
DOI: 10.1371/journal.pone.0157844
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Secretome Profiles of Manganese(II)-Oxidizing Ascomycete Fungi

Abstract: Fungal secretomes contain a wide range of hydrolytic and oxidative enzymes, including cellulases, hemicellulases, pectinases, and lignin-degrading accessory enzymes, that synergistically drive litter decomposition in the environment. While secretome studies of model organisms such as Phanerochaete chrysosporium and Aspergillus species have greatly expanded our knowledge of these enzymes, few have extended secretome characterization to environmental isolates or conducted side-by-side comparisons of diverse spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 65 publications
1
29
0
3
Order By: Relevance
“…In the current research the molecular identification of the chitosanase producer fungal isolate showed 99% similarity with Dothideomycetes sp. Kirk et al, [25] reported that Dothideomycetes was the largest and the most diverse class of Ascomycetes and it was reported to produce chitosanase by Ramos-Garza et al, [26] and Zeiner et al, [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the current research the molecular identification of the chitosanase producer fungal isolate showed 99% similarity with Dothideomycetes sp. Kirk et al, [25] reported that Dothideomycetes was the largest and the most diverse class of Ascomycetes and it was reported to produce chitosanase by Ramos-Garza et al, [26] and Zeiner et al, [27].…”
Section: Discussionmentioning
confidence: 99%
“…also has a cosmopolitan distribution in soil, having been found in several environments around the world. This species also has shown potential as agents for biological control and as producers of antimicrobial metabolites, showing success in the control of plant pathogens (Zeiner et al 2016). However, there are no reports on the antimicrobial activity of members from the Paraconiothyrium, Cadophora, Toxicocladosporium, Penicillium and Pseudogymnoascus against X. citri.…”
Section: Identification Of Fungi Recovered From the Antarctic Soil Samentioning
confidence: 99%
“…The four organisms ( Bacillus, Pyrenochaeta, Paraconiothyrium sporulosum, and Stagonospora ) that oxidize Mn(II) through direct enzymatic activity exhibit a fairly narrow range (−20.9‰ to −23.1‰) for values of εMnOxO2. The putative enzymes involved in fungal Mn(II) oxidation are bifunctional solanapyrone synthase and/or an unspecified FAD‐binding protein for Pyrenochaeta , bilirubin oxidase for Stagonospora , and GMC oxidoreductase and/or bilirubin oxidase for Paraconiothyrium sporulosum (Zeiner, ; Zeiner et al., ). Mn(II) oxidation by Bacillus occurs via direct oxidation by a multicopper oxidase, MnxG, present in the exosporium of dormant Bacillus spores.…”
Section: Discussionmentioning
confidence: 99%